Division, result and score margin alter the physical and technical performance of elite wheelchair tennis player - Mason, B. S.; van der Slikke, R. M. A.; Hutchinson, M. J.; Goosey-Tolfrey, V. L. (Journal of Sports Sciences, 2020)
This study determined the physical and technical demands of elite wheelchair tennis (WT) match-play, how the demands differed between divisions (Men, Women, Quad) and the effect that set result and score margin had on these demands. Seventeen WT players were monitored during a singles competition. Physical measures of performance were analysed using an indoor tracking system and inertial measurement units. Technical measures of performance were examined using video analysis. Physical measures of performance differed by division (Men > Women > Quad) for most parameters. Rallies were longer during Men`s (P = 0.027) and Women`s (P = 0.004) matches compared to Quad`s and fewer shots were hit off 2 bounces in Men`s matches compared to Women`s and Quad`s (P = 0.026). High-speed activity (HSA) increased during losing sets (P = 0.043). Most physical measures of performance increased by moderate to large effects during sets with a small score margin (=3 games differential). Mean speed and HSA were similar during losing sets, regardless of margin, but decreased (large effects) when winning by a large margin. This study demonstrated the physical and technical demands that elite WT players need to be prepared for and how situational factors can influence these demands.